Splicing Interruption by Intron Variants in CSNK2B Causes Poirier–Bienvenu Neurodevelopmental Syndrome: A Focus on Genotype–Phenotype Correlations - Zhang, Wen; Ye, Fanghua; Chen, Shimeng; Peng, Jing; Pang, Nan; Yin, Fei (Frontiers in Neuroscience, 2022)
CSNK2B has recently been identified as the causative gene for Poirier-Bienvenu neurodevelopmental syndrome (POBINDS). POBINDS is a rare neurodevelopmental disorder characterized by early-onset epilepsy, developmental delay, hypotonia, and dysmorphism. Limited by the scarcity of patients, the genotype–phenotype correlations in POBINDS are still unclear. In the present study, we describe the clinical and genetic characteristics of 8 individuals with POBINDS, most of whom suffered developmental delays, generalized epilepsy, and hypotonia. Minigene experiments confirmed that two intron variants (c.367+5 G>A and c.367+6 T>C) resulted in the skipping of exon 5, leading to a premature termination of mRNA transcription. Combining our data with the available literature, the types of POBINDS-causing variants included missense, nonsense, frameshift, and splicing, but the variant types do not reflect the clinical severity. Reduced casein kinase 2 holoenzyme activity may represent a unifying pathogenesis. We also found that individuals with missense variants in the zinc finger domain had manageable seizures (p = 0.009) and milder intellectual disability (p = 0.003) than those with missense variants in other domains of CSNK2B. This is the first study of genotype–phenotype correlation in POBINDS, drawing attention to the pathogenicity of intron variants and expanding the understanding of neurodevelopmental disorders.